2020
DOI: 10.1016/j.impact.2020.100212
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of twenty metal, metal oxide, and metal sulfide nanoparticles' impact on differentiated Caco-2 monolayer integrity

Abstract: The use of engineered nanomaterials (ENMs) in foods and consumer products is rising, increasing the potential for unintentional ingestion. While the cytotoxicity of many ENMs has been investigated, less attention has been given to adverse impact on the intestinal barrier integrity. Chronical disruption of gastrointestinal integrity can have far reaching health implications.Using fully differentiated Caco-2 cells, the perturbation of intestinal barrier function and cytotoxicity were investigated for 20 metal, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…A wide range of zeta potential values was observed across the different types of particles suspended in water: −69 mV to 48 mV. The zeta potential for particles in cell media at both at 0 and 24 h changed significantly, as compared to the NPs in water, suggesting that the cell media components (e.g., proteins) shielded the original particle surface charge ( Table 2 ) [ 77 , 78 ].…”
Section: Resultsmentioning
confidence: 99%
“…A wide range of zeta potential values was observed across the different types of particles suspended in water: −69 mV to 48 mV. The zeta potential for particles in cell media at both at 0 and 24 h changed significantly, as compared to the NPs in water, suggesting that the cell media components (e.g., proteins) shielded the original particle surface charge ( Table 2 ) [ 77 , 78 ].…”
Section: Resultsmentioning
confidence: 99%
“…92 The mechanism of penetration is believed to be via disruption of TJs in-line with a report by Mortensen et al , revealing that Ag/SiO 2 NPs could increase the permeability coefficient of the intestinal epithelium by disrupting tight junction integrity. 93 While these works are of academic interest, the uncertainty of the fate of Au and Ag NPs and their eventual toxicity over time might not make them the ideal candidates for the future.…”
Section: Nanoparticlesmentioning
confidence: 99%
“…Intestinal barrier function is the first line of defense against harmful microbial pathogens and antigens. It has been shown that stress impairs the integrity of tight connections (Awad et al, 2017;Mortensen et al, 2020), thereby increasing the permeability of the intestinal mucosa and disrupting its function as a selective barrier to absorb nutrients and keep pathogens out. Activation of intestinal signaling pathway, such as TGF-β and Wnt, could mediate a protective strategy to maintain the functional state of intestinal barrier (Zhi et al, 2017;Liu et al, 2020).…”
Section: Bshx Decoction Improves the Intestinal Barrier By Decreasing...mentioning
confidence: 99%